Chemical structure-based design of triboelectric materials for high-performance TENGs. (1st December 2022) - Shang, Yingshuang; Wang, Zhaoyang; Yu, Chang; Xu, Wenhan; Chen, Zheng; Jiang, Bo; Zhang, Haibo
Abstract: Triboelectric nanogenerator (TENG) has attracted much interest due to its efficiency, flexibility and cost-effectiveness to harvest wasted mechanical energy. However, the relationship between the chemical composition and output performance of triboelectric materials is still not completely revealed. As an attempt to understand the structure-performance relationship at the molecular level, representative fluorinated poly (arylene ether)s with varying content of electron-donating groups (fluorene groups) in the backbone are synthesized and compared in the performance of TENGs. The structure-dependent performance of triboelectric materials in TENGs is closely related to the potential energy difference (∆ E ) between the HOMO energy level of the positive material and the LUMO energy level of the negative material. With an introduction of 50 mol% fluorene groups and the smaller ∆ E, the fluorinated poly (arylene ether) (DFAFW50) contacting with PEEK provides the best output performance of the TENG, and remains stable output performance in 120, 000 cycles. For fluorinated poly (arylene ether)s, the introduction of electron-donating groups makes materials tend to lose electrons. Within this effort, a potential molecular design protocol is proposed to develop high-performance positive and negative triboelectric materials applicable in TENGs. Graphical Abstract: ga1 Highlights: TENGs based on fluorinated poly (arylene ether)s with varying fluorene groups are built and compared. The fluorene groups could introduce traps, thereby improving the output performance of fluorinated poly (arylene ether)s. The smaller ∆E between HOMO and LUMO energy level of triboelectric materials interprets the TENG performance enhancement. A bridge among TENG property, molecular structure and orbital energy level is built to direct triboelectric material design.